The Effect of Financial Technology on the Financial Satisfaction of MSMEs in Malang - Erna Retna Rahadjeng; Yulist Rima Fiandari (Universitas muhammadiyah malang, 2022)
This study aims to determine the effect of financial technology on financial satisfaction of Small Businesses (SMEs) in Malang City. By using primary data and random sampling, as well as using a questionnaire distributed to entrepreneurs and measured with a Likert scale. The collection of data on MSME respondents in the city of Malang is based on the distribution of questionnaires. The research objectives are as follows: To know the influence of Fintech on financial satisfaction?”. The analytical method used to determine the effect is to use simple regression statistics, with regression analysis tools used SPPS tools. The results obtained from the regression analysis show that there is a significant influence between Fintech variables on Financial Satisfaction. This is indicated by the value of the coefficient of determination (Adj.R-square) generated by the Fintech regression model (effect of feature convenience, social influence, performance expectations, system security and payment system drivers) on financial satisfaction of 0.565. Simultaneous testing of the hypothesis of the influence of Fintech variables (Ease of Features, Social Influence, Performance Expectations, System Security and Payment System Drivers) on Financial Satisfaction resulted in an F-test statistic of 26,716 with a probability of 0.000. This means that there is a simultaneous significant influence (together) with Fintech (Feasibility of Features, Social Influence, Performance Expectations, System Security and Payment System Drivers) on Financial Satisfaction.